A Study on a Fully Integrated Coil Based on the LCCL-S Compensation Topology for Wireless EVs Charging Systems - Junchen Xie; Guangyao Li; Seungjin Jo; Dong-Hee Kim (Applied Sciences, 2023)
This study proposes a full integration method for the double capacitances and inductance–series (LCCL-S)-compensated inductive power transfer (IPT) of electric vehicles (EVs). The transmitter and receiver coils adopt the unipolar coil, and the compensation inductor is designed as an extended DD coil. Specifically, the use of an extended DD coil enhances the misalignment tolerance of the EVs. When the IPT system is in the misaligned state, a primary transfer path for magnetic flux is established between the transmitter and receiver coils, and a secondary transfer path is established between the extended DD coil and receiver coil. The distance between the two unipolar coils of the extended DD coil is optimized to maximize the magnetic flux on the secondary transfer path, thereby increasing the total power of the system misaligned state. Simultaneously, the most suitable turns and inner diameter of the extended DD coil are designed by using the finite element method (FEM) simulation tool. In order to verify the performance of the proposed integrated coil method, a 3.3 kW experimental prototype with a 100 mm air gap was constructed and compared with the conventional integration method under the same conditions. The experimental results show that the proposed magnetic coupling structure maintains at least a 63.6% well-aligned value at a door-to-door 150 mm misaligned state, and the output power of the system is 1.05 kW higher than that of the traditional integration method without extra control algorithms.